PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KINERJA LINGKUNGAN TERHADAP FINANCIAL DISTRESS (STUDI KASUS PADA PERUSAHAAN SEKTOR BASIC MATERIAL PERIODE 2018-2022) - Anisa Dwi Amalia; Vita Citra Mulyandini (ITB AAS Indonesia Surakarta, 2024)
Financial distress is a situation in which a firm experiences a deterioration in its financial performance such that it has difficulty carrying out its operational activities and meeting its obligations. The objective of this study was to determine the effects of institutional ownership and environmental performance on financial distress both simultaneously and partially. The population of this study is companies in the basic materials sector that are listed on the Indonesia Stock Exchange during the period 2018-2022. The sampling method used is purposive sampling. The total sample of this study consists of 90 companies. Multiple linear regression analysis using SPSS version 25 was used for data analysis. The results of this study show that institutional ownership and environmental performance have no simultaneous influence on financial distress. Institutional ownership and environmental performance have no partial influence on financial distress.